The Ethanol Extract of Neem Leaf (Azadirachta Indica A. Juss) Effect towards Wound Healing in Male Swiss Webster Mice - Mustamu, Hillary L.; Evacuasiany, Endang; Liana, Laella K. (Journal of Medicine and Health, 2016)
accelerates wound healing. We examined the effect of Ethanol Extract of Neem Leaf (EENL) inaccelerating wound healing and compared its potential with povidone iodine. This was ananalytic experimental study, using Complete Randomized Design (CRD) with a comparativemethod. We used 30 male Swiss Webster mice that were divided into five groups (n=6). Eachgroup was given the Ethanol Extract of Neem Leaf (EENL) with a concentration of 25%, 12.5%and 25%, aquades (negative control) and povidone iodine 10% (comparison). The averagewound healing time of EENL 25%, EENL 12.5% , EENL 6.25% , povidone iodine and aquadeswere 11.2; 12.2;13.2;13.2;and 1.3 days respectively. The data was analized with one wayANOVA and showed a highly significant difference of p=0.000. Tukey HSD test showed thatEENL 25% and 12.5% had better potential than povidone iodine 10% and EENL 6.25% had thesame potential with povidone iodine 10%. This study concludes that ethanol extract of neem leafhas an effect in accelerating the duration of wound healing, with EENL 25% as the bestconcentration in accelerating the duration of wound healing.Keywords: neem leaf, Azadirachta indica A. Juss, wound healing, Swiss Webster mice